Hepatitis E Virus Infection, a Risk for Liver Transplant Recipients in Sweden. Issue 12 (11th November 2022) - Frankal, Miriam; Skoglund, Catarina; Castedal, Maria; Lagging, Martin; Norder, Heléne
Abstract : Background: Following exposure to hepatitis E virus (HEV), liver transplant (LT) recipients have an increased risk of developing chronic infection, which may rapidly progress to severe liver damage if not treated. The prevalence of HEV infection after LT is unclear and likely varies geographically. The aim of this study was to investigate the prevalence of acute and chronic HEV infection among LT recipients in an HEV endemic region. Methods: During 2013 to 2015, 109 of 152 prospectively enrolled patients listed for LT received a liver graft and completed the study protocol. They were evaluated for anti-HEV IgM, HEV IgG, and HEV RNA at the time of LT assessment and 3 and 12 mo post-LT. Medical records were reviewed. Results: Twelve (11%) LT recipients acquired markers of HEV infection during the study period. Seven patients (6%) had detectable HEV RNA, 1 before LT and 3 at the 3-mo and another 3 at the 12-mo follow-up post-LT. All resolved their infections without treatment and had undetectable HEV RNA at the succeeding follow-up. Another 5 (5%) patients developed anti-HEV antibodies without detectable HEV RNA as an indication of HEV infection during follow-up. Signs and symptoms of HEV infection were subtle‚ and none were diagnosed in routine clinical care. Conclusion: A substantial proportion of LT recipients in Sweden are at risk of acquiring HEV infection, both before and after LT. The results highlight the frequency of silent, spontaneously resolving HEV infections and do not support universal screening of LT recipients in Sweden, despite HEV being a potentially treatable infection. Abstract :